Does humility facilitate knowledge sharing? Investigating the role of humble knowledge inquiry and response. Issue 6 (12th August 2019) - Anand, Amitabh; Walsh, Isabelle; Moffett, Sandra
Abstract : Purpose: Despite the strong focus on virtues in firms, humility is little recognized in the management literature and, more particularly in the literature about knowledge sharing (KS). Despite efforts to foster KS among employees in firms, the effectiveness of this process narrows down to the dyadic relationship between the knowledge seeker and provider within firm. This paper aims to investigate the role of humility in the KS process in dyadic activity. Design/methodology/approach: The authors undertake an exploratory investigation to fill some of the gaps found in the literature. The paper draws insights from psychology, history, religion, current events and management literature. Findings: The authors identify several individual propensities that help predict humility towards sharing knowledge from seeker (humble knowledge-inquiry) and provider perspectives (humble response). They propose a new conceptual process model of KS with humility as an important variable to consider. This work highlights several promising directions for future research. Originality/value: As per the authors' knowledge, this is the first paper that investigates the role of humility in knowledge sharing from dyadic perspective. The authors also introduce concepts of humble knowledge inquiry and humble response in a dyadic context for effective knowledge sharing process.